Perancangan Sistem Informasi Geografis Pemetaan Kantor Pelayanan JNE Berbasis Android - Eva Itma Anna; Ahmad Ihkwan; Roby Kurniawan (Jurnal Teknologi dan Informatika (JEDA), 2021)
AbstractThe development of information technology has been growing rapidly, this can be seen from the number of intelligent computers that can be used to help human movement space as well as in solving various problems. The city of Bandar Lampung at this time continues to improve and develop services in all fields, especially in the field of delivery services. To meet the needs needed in geographic information system research, the search for JNE service offices will later be able to facilitate the public in finding the location and information of the desired delivery service. After going through several stages of analysis of the geographic information system design, the mapping of the JNE service office can run according to the initial objectives of the research. This information system can make it easier for users to find JNE offices and JNE representatives, especially in the Bandar Lampung area, able to search for the closest route to the JNE office that you want to visit and make it easier to find JNE offices near the user because it is displayed in map form on google maps.